Change in antimicrobial susceptibility of Listeria spp. in response to stress conditions - Wang, Haoqiu; Feng, Mengyao; Anwar, Tanveer Muhammad; Chai, Wenqin; Ed-Dra, Abdelaziz; Kang, Xiamei; Rantsiou, Kalliopi; Kehrenberg, Corinna; Yue, Min; Li, Yan (Frontiers in Sustainable Food Systems, 2023)
Listeria species are exposed to various stressors throughout the food chain, which are crucial for microbe mitigation strategy in the food industry. However, the survival capabilities and development of antimicrobial resistance by Listeria spp. under different food processing environments (FPEs) stressors are not yet well understood. Hence, this study aims to determine the difference in survivability and antimicrobial susceptibility of L. monocytogenes (Lm) and other Listeria species (non-Lm) strains exposed to different FPEs stressors, including heat, acidic and alkaline pH, UV irradiation, and osmotic stress. For this, a collection of 11 Lm and 10 non-Lm strains were used to conduct experiments. This study showed that Lm strains were relatively more tolerant to environmental stresses than non-Lm strains (p > 0.05). Additionally, the evaluation of stress-induced resistance toward antimicrobials showed that anaerobic incubation, after exposition to environmental stresses, rendered Lm and non-Lm more resistant to antimicrobial agents than aerobic incubation. Furthermore, the study observed that different stressors induced an increase in minimum inhibitory concentrations (MICs) of certain antimicrobials. Specifically, heat stress persuaded an increase in MICs of tetracycline under aerobic incubation, and gentamicin and ciprofloxacin under anaerobic incubation. Acidic/alkaline pH induced an increase in MICs of gentamicin, ciprofloxacin, and trimethoprim-sulfamethoxazole, especially under anaerobic incubation. However, UV stress induced increase in MICs of tetracycline and trimethoprim-sulfamethoxazole under aerobic incubation and gentamicin, ciprofloxacin, and trimethoprim-sulfamethoxazole under anaerobic incubation. Additionally, osmotic stress induced an increase in MICs of tetracycline and ampicillin under aerobic incubation and gentamicin, tetracycline, and trimethoprim-sulfamethoxazole under anaerobic incubation. Collectively, this study highlights that stress tolerance may contribute to the predominance of Listeria species among FPEs and induce the development of antimicrobial resistance even without antibiotic selection pressure. The findings of this study may guide updated strategies to mitigate Listeria species in the food industry.